A percepção de professores da educação infantil e do ensino fundamental I no tocante à discussão de gênero no espaço escolar - Silva, José Eudemayke da (Universidade Federal Rural do Semi-Árido, 2020)
The present study discusses the discussion of gender in the school context, especially in the field of Early Childhood Education and Elementary School I, a theme that has generated a great obstacle in relation to the dialogue / discussion between students, teachers and educators in general. This requires the perception of teachers at this school level, on the topic, under discussion, in one of the schools in the municipality of Santana do Matos / RN. In view of this, we emphasize some objectives that are relevant to the reflections and questions in this work, such as: reflecting and questioning respect for gender diversity, in the space of learning at these levels of education, verifying and identifying problems related to prejudice at school; understand how teaching work takes place in discussions about gender diversity at school. In addition, we emphasize, even though the present study intends to analyze the first impressions of gender in early childhood education, to reflect and question about the development of gender relations in school focused on diversity. In order to achieve the objectives that were set in this study, a survey was carried out, in loco, among school teachers who work in early childhood education and elementary school, in addition to using methodological procedures in the research, such as: articles, magazines and in books that discussed the subject; application of questionnaires, previously prepared, with teachers; in addition, some observations were made during the pedagogical practice of these professionals in order to identify possible discussions, conversations and inquiries regarding the aforementioned object of study in this research. In this study we support some theorists, which allowed us to reflect on the discussion of gender in the context of education, among which we can emphasize: Louro (2008), Diniz (2004), Prado (2008) and Heerdt (2003). As a result of the study, it was proposed to insert a proposal for research and studies that address a more investigative analysis on the problem under study; and presented the sample of the educational reality in force in the school space, field of research, in an attempt to contribute with new perspectives where it can lead to more critical studies andwhich allow reflections on teaching practice.
Monografia
Keywords: Gênero; Ensino Fundamental I e Educação Infantil; Inclusão social; Gender; Elementary School I and Early Childhood Education; Social inclusion; CIENCIAS EXATAS E DA TERRA::COMPUTACAO E INFORMATICA